Stability region of two-point variable step–block backward differentiation formulae. Issue 2 (June 2017) - Yatim, SAM; Asnor, AI; Ibrahim, ZB
Stability region of two-point variable step–block backward differentiation formulae method is analysed in this article where we took into consideration on the increment of step size to a factor 1.8. The stability graph for three distinct step size ratios are plotted using Maple software and presented in different graphs. The stability properties are also become part of the analysis that have been studied in this article.